The combined effect of graphene oxide and elemental nano-sulfur on soil biological properties and lettuce plant biomass - Hammerschmiedt, Tereza; Holatko, Jiri; Zelinka, Radim; Kintl, Antonin; Skarpa, Petr; Bytesnikova, Zuzana; Richtera, Lukas; Mustafa, Adnan; Malicek, Ondrej; Brtnicky, Martin (Frontiers in Plant Science, 2023)
The impact of graphene oxide (GO) nanocarbon on soil properties is mixed, with both negative and positive effects. Although it decreases the viability of some microbes, there are few studies on how its single amendment to soil or in combination with nanosized sulfur benefits soil microorganisms and nutrient transformation. Therefore, an eight-week pot experiment was carried out under controlled conditions (growth chamber with artificial light) in soil seeded with lettuce (Lactuca sativa) and amended with GO or nano-sulfur on their own or their several combinations. The following variants were tested: (I) Control, (II) GO, (III) Low nano-S + GO, (IV) High nano-S + GO, (V) Low nano-S, (VI) High nano-S. Results revealed no significant differences in soil pH, dry plant aboveground, and root biomass among all five amended variants and the control group. The greatest positive effect on soil respiration was observed when GO was used alone, and this effect remained significant even when it was combined with high nano-S. Low nano-S plus a GO dose negatively affected some of the soil respiration types: NAG_SIR, Tre_SIR, Ala_SIR, and Arg_SIR. Single GO application was found to enhance arylsulfatase activity, while the combination of high nano-S and GO not only enhanced arylsulfatase but also urease and phosphatase activity in the soil. The elemental nano-S probably counteracted the GO-mediated effect on organic carbon oxidation. We partially proved the hypothesis that GO-enhanced nano-S oxidation increases phosphatase activity.